(untitled) (Applied Biological Research, 2014)
Present investigation was conducted on Sahiwal, HF crosses and Murrah bulls maintained at A.B. Complex, NDRI, Karnal (India) to identify the relative efficiency of various sterilization methods for the treatment of artificial vagina (AV) to be used for bovine semen processing. The glassware part of AV was sterilized by hot air oven at 1600C for 60 min. and microwave oven for 3 min. A total of 72 ejaculates were taken from 3 collections each from 4 bulls of each breed/species subjected to 2 types of treatments, then total plate count (TPC) of all these combinations was carried out using plate count agar media. Standardization of the best sterilizing method was done by selecting the method whose total bacterial count on the media was the least and the best semen quality (mass activity, initial motility, non-eosinophilic percent and abnormalities) was obtained. The microwave oven method of sterilization of glassware part of artificial vagina was found superior over hot air oven method.